Keberagamaan Otentik dalam Al-Qur’an - Hamim Ilyas (Balai Penelitian dan Pengembangan Agama Semarang, 2014)
AbstractMulti-dimensional crisis experienced by the muslims are related to their religiosity. To overcome the crisis, they need develop authentic religiosity. This research examines the authentic type of religiosity taught by the Qur’an with the method of tafsir (Qur’anic interpretation). The study found that the religiosity taught by the Qur’an is ethicalreligiosity which manifests in two frameworks: works and capacity. The first framework consists of two works: first, total surrender in God in term of comprehending and submitting to God’s will manifested in His qauliyya (speech), kauniyya (universe), and tarikhiyya (history) verses. Second, following the milla (religion) of Abraham. The secondframework consists of five capacities: muhsin (social capacity), hanif (moral capacity),muslim (intelectual capacity), qanit (spiritual capacity), and syakir (personal capacity).Keywords: Authentic religiosity, Islam, the Qur’anAbstrakKrisis multi dimensi yang dialami umat Islam berhubungan dengan keberagamaan mereka. Untuk mengatasinya mereka harus mengembangkan keberagamaan otentik. Penelitian ini mengkaji tipe keberagamaan otentik yang diajarkan al-Qur’an denganmetode tafsir. Ditemukan bahwa tipe keberagamaan yang diajarkan al-Qur’an adalah keberagamaan etis yang terwujud dalam dua kerangka: amal dan kapasitas. Kerangka pertama terdiri atas dua amal. Pertama, berserah diri kepada Allah dalam pengertianmemahami dan tunduk kepada kehendak-Nya yang diungkapkan dalam ayat-ayat qauliyah, kauniyah dan tarikhiyah. Kedua, mengikuti Millah Ibrahim. Kemudian kerangka kedua terdiri atas lima kapasitas: muhsin (kapasitas sosial), hanif (kapasitas moral), muslim (kapasitas kecendekiaan), qanit (kapasitas spiritual) dan syakir (kapasitas personal.)Kata kunci: Keberagamaan otentik, Islam, al-Qur’an